The Relationship Antecedents of Smoking (RAS) Scale: A new scale to assess couple-focused triggers to smoke. - Erin Tooley; Joseph L. Fava; Belinda Borrelli (New Prairie Press, 2023)
The purpose of this pilot study is to assess the reliability and construct validity of a measure of relationship-focused antecedents for smoking (RAS). The scale includes both positively-valenced items (e.g.. "I feel like smoking when I am relaxing with my partner") and negatively-valenced items (e.g., "I feel like smoking when my partner criticizes me"). Participants included 123 individuals who smoke cigarettes with co-habitating smoking (n=63) or non-smoking (n=60) romantic partners. Participants completed the RAS and a series of measures associated with smoking outcomes. Principal component analysis with varimax rotation resulted in a 2-component solution. The RAS showed excellent internal consistency for the total scale (α=.96) and for the positive (α=.88) and negative (α=.97) subscales. Higher positive subscale scores were associated with lower motivation to quit while higher negative scores were associated with lower relationship satisfaction and dyadic efficacy to quit. Higher scores on both subscales were related to higher social motives, dependence motives, and social outcome expectances. Participants with smoking partners reported higher positive subscale scores and lower negative subscale scores. The RAS may be helpful in the design of smoking cessation interventions for couples.